2016
DOI: 10.1136/jmedgenet-2015-103511
|View full text |Cite
|
Sign up to set email alerts
|

Mutations inEXOSC2are associated with a novel syndrome characterised by retinitis pigmentosa, progressive hearing loss, premature ageing, short stature, mild intellectual disability and distinctive gestalt

Abstract: We report a novel condition that is probably caused by altered RNA exosome function and expands the spectrum of clinical consequences of impaired RNA metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
122
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(127 citation statements)
references
References 18 publications
1
122
0
1
Order By: Relevance
“…Conversely, seizures and spasticity, which have been reported in families 1 and 2, respectively, were not observed in the German patients. Minor anomalies in faces such as prominent forehead and broad nasal tip have been found in both German and Iranian patients . As we found the novel variant c.673‐1G > T in intron 7 of EXOSC2 in two unrelated families located in two different provinces which share a long border, it might be an implication of a founder effect in the Iranian population.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Conversely, seizures and spasticity, which have been reported in families 1 and 2, respectively, were not observed in the German patients. Minor anomalies in faces such as prominent forehead and broad nasal tip have been found in both German and Iranian patients . As we found the novel variant c.673‐1G > T in intron 7 of EXOSC2 in two unrelated families located in two different provinces which share a long border, it might be an implication of a founder effect in the Iranian population.…”
Section: Discussionsupporting
confidence: 50%
“…The EXOSC gene family is involved in the RNA exosome complex which is evolutionarily conserved with catalytic and structural subunits degrading and/or processing a wide variety of RNA species . Mutations in RNA exosome genes have recently been linked to distinct syndromes with tissue‐specific disorders …”
Section: Introductionmentioning
confidence: 99%
“…In the last 2 years several other studies indicated that mutations in EXOSC3 result in a more variable clinical presentation, suggesting that exosome complex dysfunction is a major cause of severe childhood onset complex inherited neurological disorders. More recently, also mutations in EXOSC2 found in two unrelated German families were shown to cause neurodevelopmental defects such as mild cerebellar atrophy and cerebellar hypoplasia, diffuse dysmyelination, hearing loss, mild intellectual disability, facial anomalies and premature ageing (20). …”
Section: Introductionmentioning
confidence: 99%
“…These molecular functions are best defined in yeast, but many are conserved in human cells (Staals and Pruijn, 2011). In human patients, different mutations that affect RNA exosome activity are associated with distinct human diseases: multiple myeloma (Weissbach et al, 2015), pontocerebellar hypoplasia (Boczonadi et al, 2014; Wan et al, 2012), trichohepatoenteric syndrome (Fabre et al, 2012; Hartley et al, 2010), and most recently, a distinct disorder that has not yet been named (Di Donato et al, 2016). A thorough investigation of the structure and function of the RNA exosome is essential to understand how the RNA exosome carries out all of these functions, and how RNA exosome defects cause these very diverse diseases.…”
Section: Introductionmentioning
confidence: 99%